Growth and informality: An empirical analysis of the role of the informal sector in the Moroccan economy - MOUFID , Fahd; BOUSSEDRA , Faouzi (Revue Internationale du Chercheur, 2025)
Abstract This article analyzes the impact of the informal sector on economic growth in the Moroccan context using two distinct econometric approaches: DSGE and MIMIC. The study covers the period from 1996 to 2022 and focuses on the relationship between the size of the informal sector and GDP per capita, with the aim of evaluating how informality influences Morocco's economic performance. The results obtained from these two econometric models, clearly and significantly indicate that an increase in the size of the informal sector negatively affects economic growth. The DSGE approach reveals that an increase of one unit in the relative size of the informal sector leads to a decrease of 12.51 units in the logarithm of GDP per capita, while the MIMIC approach yields even stronger results, with a reduction of 15.78 units. These coefficients highlight the strong elasticity of economic growth with respect to the expansion of informality, indicating that informality plays a significant role in reducing economic performance. The empirical analysis of Moroccan data confirms the hypothesis that the informal sector is a major barrier to the country's economic growth. These results corroborate existing economic theories that emphasize the harmful effects of informality on productivity, access to financing, and tax revenue collection. The study calls for a greater awareness of the importance of adopting institutional and fiscal reforms in Morocco to encourage the transition from the informal sector to the formal economy, which could serve as a key lever to promote sustainable and inclusive growth, essential for Morocco's economic future.